Constructing film composites of silicon nanowires@CdS quantum dot arrays with ameliorated photocatalytic performance. (3rd August 2018) - Lin, Xin; Li, Shao-Hai; Lu, Kang-Qiang; Tang, Zi-Rong; Xu, Yi-Jun
Abstract : The film composites of n-type CdS QD decorated p-type silicon nanowire arrays are assembled toward H2 evolution with improved photoactivity and photostability. Abstract : Silicon nanostructure-based composites have recently aroused intensive interest because of their promising potential to convert solar energy into chemical fuels. Here, we report a facile approach to construct the film composites of n-type CdS quantum dot (QD) decorated p-type vertically aligned one-dimensional (1D) silicon nanowire (SiNWs@CdS) arrays with enhanced activity and recyclable operability for photocatalytic hydrogen evolution in comparison with the single component counterpart. The photoelectrochemical results confirm the formation of a p–n heterojunction in the interface of SiNWs and CdS QDs, which can create an internal electric field to facilitate the separation and transport of photoinduced charge carriers, thereby leading to the concomitant improvement of both the photoactivity and photostability of the SiNWs@CdS array composite. This work is expected to provide an instructive recipe for fabricating p–n heterojunction 1D-based composite arrays with a film structure to boost charge carrier separation and transfer, and to achieve efficient artificial solar energy conversion.